2016
DOI: 10.1590/1983-21252016v29n125rc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameter Estimates for Production and Reproduction Traits in Dairy Buffaloes

Abstract: -The objective of this study was to determine the genetic variation in milk production, milk components, and reproductive traits in dairy buffaloes. A total of 9,318 lactation records from 3,061 cows were used to estimate the heritability of milk yield (MY), fat percentage (%F), protein percentage (%P), lactation length (LL), calving interval (CI), and age at first calving (AFC), as well as genetic and phenotypic correlations between these traits. Covariance components were estimated by Bayesian inference in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 10 publications
8
17
4
Order By: Relevance
“…These results are in close agreement with the findings of Kumar et al, (2001) and Suresh et al, (2004). Higher and positive genetic correlation between LL and CI was supported by the findings of Barross et al, (2016) indicating that increase in LL will result in selection for longer CI. Tonhati et al, (2000b) and Aziz et al, (2001) found low genetic correlations between these traits (-0.20 and 0.09, respectively).…”
Section: Resultsmentioning
confidence: 73%
“…These results are in close agreement with the findings of Kumar et al, (2001) and Suresh et al, (2004). Higher and positive genetic correlation between LL and CI was supported by the findings of Barross et al, (2016) indicating that increase in LL will result in selection for longer CI. Tonhati et al, (2000b) and Aziz et al, (2001) found low genetic correlations between these traits (-0.20 and 0.09, respectively).…”
Section: Resultsmentioning
confidence: 73%
“…Similar to present results (Mourad and Khattab, 2009), (Ibrahim et al, 2012), (EL-Arian et al, 2012) and (Shalaby et al, 2013) recorded that high positive genetic correlation between days in milk and milk yield. The opposite results obtained by (Barros et al, 2016) reported that low negative correlation between days in milk and milk yield.…”
Section: Discussionmentioning
confidence: 69%
“…These results agreed with (Amin and Alhur, 2011) and (El-Bramony, 2014). The opposite results obtained by (Aziz et al, 2001), (Thevamanoharan et al, 2002), (Badran et al, 2005), (Kawthar et al, 2005), (El-Bramony, 2011), (Malhado et al, 2013) and (Barros et al, 2016) who recorded low heritability estimates for days open and calving interval.…”
Section: Discussionmentioning
confidence: 89%
“…The number of buffaloes (Bubalus bubalis) have been increasing in the Brazilian livestock due to their rusticity, longevity, high adaptive capacity to adverse conditions (Joele et al, 2013;Barros et al, 2016;Santos et al, 2016) and resistance to diseases and endo and ectoparasites (Hurtago-Lugo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, dairy products from buffalo milk, such as yogurts, cheeses, ricotta and especially mozzarella, have reached high market values (Araújo et al, 2012;Barros et al, 2016). Therefore, the need for investments in sanitary, Pesq.…”
Section: Introductionmentioning
confidence: 99%